2019
DOI: 10.22435/hsji.v12i2.2449
|View full text |Cite
|
Sign up to set email alerts
|

HDAC2 and PCNA expression is correlated to decreasing of endoxifen sensitivity in human breast cancer stem cells ALDH+

Abstract: HDAC2 and PCNA expression correlated to endoxifen resistancy 77 HDAC2 and PCNA expression is correlated to decreasing of endoxifen sensitivity in human breast cancer stem cells ALDH+ Abstrak Latar belakang: Sel punca kanker payudara (breast cancer stem cells/BCSC) adalah subpopulasi sel kanker yang memiliki kemampuan menghasilkan tumor baru dan bersifat seperti sel punca. Penelitian kami sebelumnya menggunakan jaringan kanker payudara mengungkapkan bahwa ekspresi gen histone deacetylase 2 (HDAC2) dan prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
2
0
0
Order By: Relevance
“…PCNA serves as an indicator of cancer severity-progression. The number of PCNAs in this study proved the success of DMBA induction in the OSCC rat model (Sadikin, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…PCNA serves as an indicator of cancer severity-progression. The number of PCNAs in this study proved the success of DMBA induction in the OSCC rat model (Sadikin, 2019).…”
Section: Discussionsupporting
confidence: 62%
“…4d). Some studies further reported that the deubiquitylation-mediated stabilization of PCNA is crucial for multiple processes, such as upregulating mutagenesis and regulating the function of cancer stem cells [73,75]. Taking advantage on our experiments, the ubiquitylation of PCNA was significantly upregulated in USP1-inhibited cells (Fig.…”
Section: Discussionsupporting
confidence: 54%